In Silico Genome-Wide Analysis Reveals the Potential Links Between Core Genome of Acidithiobacillus thiooxidans and Its Autotrophic Lifestyle - Zhang, Xian; Liu, Zhenghua; Wei, Guanyun; Yang, Fei; Liu, Xueduan (Frontiers in Microbiology, 2018)
The coinage ‘pan-genome’ was first introduced dating back to 2005, and was used to elaborate the entire gene repertoire of any given species. Core genome consists of genes shared by all bacterial strains studied and is considered to encode essential functions associated with species’ basic biology and phenotypes, yet its relatedness with bacterial lifestyle of the species remains elusive. We performed the pan-genome analysis of sulfur-oxidizing acidophile Acidithiobacillus thiooxidans as a case study to highlight species’ core genome and its relevance with autotrophic lifestyle of bacterial species. The mathematical modeling based on bacterial genomes of A. thiooxidans species, including a novel strain ZBY isolated from Zambian copper mine plus eight other recognized strains, was attempted to extrapolate the expansion of its pan-genome, suggesting that A. thiooxidans pan-genome is closed. Further investigation revealed a common set of genes, many of which were assigned to metabolic profiles, notably with respect to energy metabolism, amino acid metabolism, and carbohydrate metabolism. The predicted metabolic profiles of A. thiooxidans were characterized by the fixation of inorganic carbon, assimilation of nitrogen compounds, and aerobic oxidation of various sulfur species. Notably, several hydrogenase (H2ase)-like genes dispersed in core genome might represent the novel classes due to the potential functional disparities, despite being closely related homologous genes that code for H2ase. Overall, the findings shed light on the distinguishing features of A. thiooxidans genomes on a global scale, and extend the understanding of its conserved core genome pertaining to autotrophic lifestyle.